Effects of business improvement districts on firm performance, place attractiveness, and urban safety - Sven-Olov Daunfeldt; Oana Mihaescu; Niklas Rudholm (Institute of Retail Economics (HFI), 2021)
Business improvement districts (BIDs) have emerged as possible solutions for the revitalization of urban areas characterized by economic decline. Using a difference-in differences model, we investigate the effects of a voluntary Swedish BID programme in five cities on firm performance, urban safety, and place attractiveness – both within and outside the BID. We find that the BID programme increased labour productivity for incumbent firms within the BID by 7.62%, mainly through an increase in revenues. However, the positive effect of the BID programme on firm performance is largely transitory, decreasing sharply during the third year and then becoming insignificant. We find no statistically significant impacts on firm performance outside the geographical boundaries of the BIDs. The results also suggest that fewer crimes were committed in the BIDs, as the estimates for all years are negative, though they are significant only for the fourth year after BID implementation. Finally, we detect no statistically significant effects of the BID programme on property values either within or outside the designated BIDs.
Keywords: H44; L11; L25; R11; R12; 330; Business improvement district; public–private partnerships; firm performance; labour productivity; property values; crime; difference-in-differences